Are multiple-choice tests a sufficient tool for the assessment of knowledge? - Űlen, Simon; Slavinec, Mitja (Anali PAZU, 2022)
How best to assess students’ knowledge is still an unsolved dilemma among educational researchers. Multiple-choice questions become a popular assessment tool at all stages of education. But, many researchers are sceptical if such assessment is sufficient for the determination of students’ knowledge. In this paper, we present our study, in which 167 students of Physiotherapy were involved. Students had to complete a multiple-choice test after completing the physics course. The multiple-choice test incorporated questions, which covered domains of physics that were part of the course, and questions from the field of modern physics that were not part of the course. The results of this study indicate that multiple-choice questions can be a successful assessment tool for the determination of students’ knowledge.